Fundamentals of surgical practice - Kingsnorth, A. N.; Bowley, Douglas M. (Cambridge : Cambridge University Press, 2011)
"This extensively revised and updated edition of Fundamentals of Surgical Practice is a key surgical textbook for the intercollegiate MRCS examination. Mirroring the entire new syllabus, it offers trainees a clear understanding of the core knowledge required for examination success and incorporates new material reflecting recent developments and the new examination. Designed to achieve maximum efficiency in learning, the content provides ample detail with key points and suggestions for further reading. In addition to a detailed index, each chapter has its own table of contents to enhance ease of use. The contributors are acknowledged experts, many of whom are recognised in their fields as innovators, practical clinicians, and Royal College examiners. This text is indispensable for the new trainee and provides established surgeons and other healthcare professionals working in the surgical environment with a modern, authoritative overview of the key areas of surgical practice"--Provided by publisher.
13. Fundamentals of intensive care Angela L. Neville; 14. Caring for surgical patients: complications and communication Douglas M. Bowley; 15. Management of sepsis Mark J. Midwinter; Part V. Common Surgical Conditions: 16. Assessment and early treatment of the patient with trauma Ross Davenport and Nigel Tai; 17. Fundamentals of the central nervous system James Palmer and Anant Kamat; 18. Fundamentals of head and neck surgery John K. S. Woo and Walter W. K. King; 19. Fundamentals of thoracic surgery Richard S. Steyn and Deborah Harrington; 20. Fundamentals of oesophago-gastric surgery Timothy Wheatley; 21. Fundamentals of hepatobiliary and pancreatic surgery Mark Duxbury and Rowan Parks; 22. Fundamentals of endocrine surgery Peter Cant; 23. Fundamentals of the breast Steven D. Heys; 24. Fundamentals of lower gastrointestinal surgery Chris Cunningham; 25. Fundamentals of the genitourinary system Angela Cottrell and Andrew Dickinson; 26. Hernias Andrew N. Kingsnorth; 27. Fundamentals of vascular surgery Donald J. Adam, Martin W. Claridge and Antonius B. M. Wilmink; 28. Fundamentals of orthopaedics Jon Clasper; 29. Fundamentals of plastic surgery Tania C. S. Cubison; 30. Surgical care of the paediatric patient Paul K. H. Tam; 31. Fundamentals of organ and tissue transplantation Matthew Bowles; Index.
Includes bibliographical references and index.
Keywords: Surgical Procedures, Operative